Analisis Pengembangan Porang sebagai Hasil Hutan Bukan Kayu salam Menunjang Ekonomi Rumah Tangga Masyarakat di Desa Golorutuk Kabupaten Manggarai Timur - Yustinus Basri; Mamie E. Pellondo’u; Pamona Silvia Sinaga (Wana Lestari, 2023)
Porang are Non-Timber Forest Products which produce tubers that can be planted in agroforestry systems. In Golo Rutuk Village, East Manggarai Regency, porang plants grow wild on private land and community forests. But so far it has not developed properly good. The purpose of this study was to determine the strategy for developing porang plants in supporting the household economy of the community in Golo Rutuk Village, East Manggarai Regency. This research was conducted in Golo Rutuk Village, East Manggarai Regency, carried out for one month, namely in September 2021. The data collection techniques used in this study were the census method, interviews with porang farmers and literature study. Analysis of the data using SWOT analysis. The results of this study indicate that the appropriate strategy for the development of porang plants in supporting the household economy in Golo Rutuk Village, East Manggarai Regency is the SO strategy (Strengths Opportunities), namely a strategy for existing strengths by taking advantage of existing opportunities, by utilizing suitable natural conditions and also a fairly easy cultivation process so that they can meet export needs which are still very high, with the many benefits and nutritional content possessed by porang plants, if followed by proper processing, it will add value to people's sales and can be used as an alternative food, as well as building partnerships between farmers and entrepreneurs/porang dealers are important in terms of cultivation and management and marketing, so that the export needs of porang can be met.